Symptoms - Larraz, José Ramón 1929-2013; Pleasence, Angela 1941-; Vaughan, Peter 1923-2016; Heilbron, Lorna 1948- (British Film Institute, 2016)
"A young woman (Lorna Heilbron) is invited to stay at the remote country mansion belonging to her girlfriend (Angela Pleasence). But the peaceful retreat is interrupted by the menacing presence of the local gamekeeper (Peter Vaughan) and events soon take a disturbing turn. This sophisticated modern gothic horror film was the official British Palme d'Or entry at the 1974 Cannes Film Festival, but it slipped into obscurity soon after. Long-considered lost, the original negatives were rediscovered by the BFI in 2014, and have now been remastered in 2K for this world-premiere release."
Bild: 1.33:1
Special features: World-premiere edition ; Newly remastered in 2K and presented in both High Definition and Standard Definition ; "From Barcelona ... to Runbridge Wells: The films of José Larraz" (Andy Starke and Pete Tombs, 1999, 24 min): career retrospective documentary, featuring interviews with Larraz, Brian Smedley-Aston and Marianne Morris ; "On Vampyres and Other Symptoms" (Celia Novis, 2011, 74 min): feature-length documentary focusing on two of Larraz's most acclaimed films ; An Interview with Angela Pleasence (2016, 10 min): revealing new interview with the star of Symptoms ; An Interview with Lorna Heilbron (2016, 18 min): the film's co-star recalls her time working with Angela Pleasence and José Larraz ; An Interview with Brian Smedley-Aston (2016, 17 min): the Symptoms editor discusses his life in film ; original theatrical trailer ; illustrated booklet with essays and film credits
Original: UK 1974
Verlagsnummer BFIB1257
Keywords: Film; DVD-Video; Blu-Ray-Disc